Medical futility and the social context. Issue 3 (June 1997) - Halliday, R
Abstract : The concept of medical futility has come to be seen in some quarters as a value-neutral trump card when dealing with issues of power and conflicting values in medicine. I argue that this concept is potentially useful, but only in a social context that provides a normative framework for its use. This social context needs to include a broad consensus about the purpose of medicine and the nature of the physician-patient relationship.